A Psicologia entre propostas de formação desde uma perspectiva histórica - Imianowsky, André Gustavo (2014)
The objective of this research has its starting point the analysis of proposals for training of psychologists. It aims to contribute to the building of a history of psychology, fromideas and projects for the establishment of the psychologist to its insertion on the reality. Through theoretical and methodological framework of historical materialism, we ve recovered two stages: a) the period of modernization in Brazil during the 1950s, when psychologists with different proposals, get unite to regulate the profession in thiscountry, one of the first to have a law to professional regulation in the area. It discusses the movement that led to the law and the importance of thinking about society/science/university relationship to define projects of training in psychology. The scenario of industrialization lived in Brazil marks the debate in various spheres of work. Inone hand, shows that there was a concern with the formation of attitudes to the world of work in a time of change. On the other, reveals that the type of activity performed by the psychologistinterests to the development of the national market; and b) a time when the 1920 EasternEurope passes through social and political change with revolutionary purpose. The discussion of psychological practice as determined for a reality and the recovery of a philosophy of psychologyappearsas ideas to think about the work of the psychologist, the plan to build a new society based on socialism shows that it was necessary tobuild a new man. The historical particularities of the contexts presented in this work, analysisfrom its ownconditions in which the debate has emerged. The training of psychologists proved to be a concern for the constitution of practice and professional identity and revealed that psychological activity deals with conservative and transformative conceptions, and may take one form or another, as well as simultaneously both